Incidencia de la migración en el rendimiento académico y abandono escolar en estudiantes de bachillerato de la unidad educativa mariscal Antonio José de Sucre de la parroquia Achupallas provincia de Chimborazo en el periodo 2019-2023. - Cucalón Vasco, Jenny Elizabeth (2025)
The study titled "Impact of Parental Migration on Academic Performance and School Dropout Among High School Students at Unidad Educativa Mariscal Antonio José de Sucre" examines the impact of parental absence because of migration on students’ academic outcomes and school retention in the Achupallas parish, Chimborazo province, during the period 2019–2023. The current research used a mixed-methods approach, the research integrates both quantitative and qualitative analyses. A non-experimental, cross-sectional, and field-based research design was used. Surveys were administered to a representative sample of students, with data analyzed using the Mann-Whitney U and Chi-square tests to identify differences in academic performance and school attendance. In addition, semi structured interviews were conducted with students, teachers, parents, and DECE (Departamento de Consejería Estudiantil) representatives, and analyzed through open, axial, and selective coding. Quantitative findings suggest that students with migrant parents face significantly greater academic challenges, including lower academic performance and higher rates of absenteeism. Qualitative results further reveal that the emotional toll of parental separation, lack of familial support, and limited institutional intervention contribute to decreased motivation and increased academic vulnerability. The study concludes that parental migration is a critical factor influencing both academic achievement and emotional well being, thereby heightening the risk of school dropout. Considering these findings, the study recommends the implementation of a comprehensive support program encompassing academic tutoring, socio-emotional counseling, and enhanced communication strategies with migrant parents.